Effect of Glycols and Glymes on Shredding Efficiency of Sodium Cellulose Crumbs and Viscose Rayon Fibre Properties - Bhagwat, V.W.; Kouto, B.B. (Asian Journal of Chemistry, 2010)
For uniform and better pulp quality, surface active agents are used in the manufacturing process of viscose rayon. In the present work it has been observed that high molecular weight glycols and glymes improve the shredding efficiency of sodium cellulose, decreases the bulk density and reduces the quantity of knots, thereby improving the quality of viscose and fibre properties of viscose rayon.